SOT1, a pentatricopeptide repeat protein with a small MutS‐related domain, is required for correct processing of plastid 23S–4.5S rRNA precursors in Arabidopsis thaliana. (3rd March 2016) - Wu, Wenjuan; Liu, Sheng; Ruwe, Hannes; Zhang, Delin; Melonek, Joanna; Zhu, Yajuan; Hu, Xupeng; Gusewski, Sandra; Yin, Ping; Small, Ian D.; Howell, Katharine A.; Huang, Jirong
Summary: Ribosomal RNA processing is essential for plastid ribosome biogenesis, but is still poorly understood in higher plants. Here, we show that SUPPRESSOR OF THYLAKOID FORMATION1 (SOT1), a plastid‐localized pentatricopeptide repeat (PPR) protein with a small MutS‐related domain, is required for maturation of the 23S–4.5S rRNA dicistron. Loss of SOT1 function leads to slower chloroplast development, suppression of leaf variegation, and abnormal 23S and 4.5S processing. Predictions based on the PPR motif sequences identified the 5′ end of the 23S–4.5S rRNA dicistronic precursor as a putative SOT1 binding site. This was confirmed by electrophoretic mobility shift assay, and by loss of the abundant small RNA 'footprint' associated with this site in sot1 mutants. We found that more than half of the 23S–4.5S rRNA dicistrons in sot1 mutants contain eroded and/or unprocessed 5′ and 3′ ends, and that the endonucleolytic cleavage product normally released from the 5′ end of the precursor is absent in a sot1 null mutant. We postulate that SOT1 binding protects the 5′ extremity of the 23S–4.5S rRNA dicistron from exonucleolytic attack, and favours formation of the RNA structure that allows endonucleolytic processing of its 5′ and 3′ ends. Significance Statement: Many of the components and processes involved in plastid ribosome biogenesis remain poorly understood. Here we identified an RNA‐binding protein that belongs to the pentatricopeptide repeat protein family and show that it facilitates plastid ribosomal RNA maturation and subsequent ribosome assembly by binding specifically to the 23S‐4.5S rRNA precursor and protecting it from exonucleolytic attack.